THE EFFECT OF SLACK RESOURCES, BOARD OF DIRECTORS FEMINISM, MEDIA EXPOSURE AND INDEPENDENT COMMISSIONERS ON CORPORATE SOCIAL RESPONSIBILITY PERFORMANCE IN THE ENVIRONMENTAL SECTOR - Fadia Khairunnisa; Yuneita Anisma; Devi Safitri (Berkala Akuntansi dan Keuangan Indonesia, 2025)
This research aims to determine the effect surplus assets, female representation in the boardroom, media visibility, and independent board of commissioners on corporate social responsibility performance in Firms registered with the Indonesia Stock Exchange (IDX) that were involved in the PROPER program between 2021 and 2023. The response variable, namely corporate social responsibility performance, is measured using the PROPER rating. The independent variable, namely Surplus resources, is measured using LN Liquid assets, The governing board directors feminism variable is measured using the percentage of female board of directors in the company, the media exposure variable is measured based on CSR disclosure on the company's website and the independent board of commissioners variable is measured using the percentage of independent commissioners in the company. The control variables used are company size, ROE, and DER. The research employed purposive sampling, resulting in as many as 256 companies. Quantitative data were employed in this study, and the analysis method was is panel data regression analysis. Employing regression analysis via the STATA application as the research method, the findings of this study demonstrate that the independent board of commissioners exerts a noteworthy positive influence on CSR performance, while slack resources, board feminism, media exposure have no effect on CSR performance. The results of this study are useful in practice to find out the deeper functions of available capital, female representation on the board, media visibility, and non-executive commissioners, employing these factors to enhance the firm's CSR performance.